2018
DOI: 10.1124/jpet.118.251157
|View full text |Cite
|
Sign up to set email alerts
|

Convulsant Effects of Abused Synthetic Cannabinoids JWH-018 and 5F-AB-PINACA Are Mediated by Agonist Actions at CB1 Receptors in Mice

Abstract: Convulsant effects of abused synthetic cannabinoid (SCB) drugs have been reported in humans and laboratory animals, but the mechanism of these effects is not known. We compared convulsant effects of partial CB1R agonist Δ 9 -tetrahydrocannabinol (THC), full CB1R agonist SCBs JWH-018 and 5F-AB-PINACA, and classic chemical convulsant pentylenetetrazol (PTZ) using an observational rating scale in mice. THC did not elicit convulsions, but both SCBs did so as effectively as and more potently than PTZ. SCB-elicited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…Although this study does not identify which pathway contributes to the toxic effects observed following SCRA consumption, our data do provide valuable insights into SCRA-mediated stimulation and inhibition of cAMP signalling in vitro. Previous studies have shown that JWH-018-AM-2201-, 5F-AB-PINACA-, and CUMYL-4CN-BINACA-induced seizures are CB1-mediated in mice, which might explain some of the toxicity experienced by recreational users of these drugs [43,44,45,46,47,48,49]. Our data shows that SCRA-induced cAMP increase was abolished after SR141716A treatment, supporting the hypothesis that SCRAs Gαs-like effects were mediated through CB1…”
Section: Discussionsupporting
confidence: 88%
“…Although this study does not identify which pathway contributes to the toxic effects observed following SCRA consumption, our data do provide valuable insights into SCRA-mediated stimulation and inhibition of cAMP signalling in vitro. Previous studies have shown that JWH-018-AM-2201-, 5F-AB-PINACA-, and CUMYL-4CN-BINACA-induced seizures are CB1-mediated in mice, which might explain some of the toxicity experienced by recreational users of these drugs [43,44,45,46,47,48,49]. Our data shows that SCRA-induced cAMP increase was abolished after SR141716A treatment, supporting the hypothesis that SCRAs Gαs-like effects were mediated through CB1…”
Section: Discussionsupporting
confidence: 88%
“…Although this study does not identify which pathway contributes to the toxic effects observed following SCRA consumption, our data do provide valuable insights into SCRA‐mediated stimulation and inhibition of cAMP signaling in vitro. Previous studies have shown that JWH‐018‐ AM‐2201‐, 5F‐AB‐PINACA‐, and CUMYL‐4CN‐BINACA‐induced seizures are CB1‐mediated in mice, which might explain some of the toxicity experienced by recreational users of these drugs . Our data shows that SCRA‐induced cAMP increase was abolished after SR141716A treatment, supporting the hypothesis that SCRAs Gα s ‐like effects were mediated through CB1 receptor.…”
Section: Discussionsupporting
confidence: 87%
“…For example, PB-22, AB-CHMINACA, and MDMB-CHMICA have been associated with generalized seizures in humans (Gugelmann et al, 2014; Hermanns-Clausen et al, 2018). In mice, 10 mg/kg 5F-AB-PINACA produces convulsions, which can be reduced by 10 mg/kg SR141716 pretreatment (Wilson et al, 2019). AM-2201 (2 mg/kg, i.p).…”
Section: Discussionmentioning
confidence: 99%